CONTESTING IGNORANCE AND REMEMBRANCE: THE IDENTITY (RE)CONSTRUCTION OF TURKISH CHARACTERS IN THE BASTARD OF ISTANBUL - Alivin, Moh. Zaimil; Huda, Miftahul (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
The issue of identity (re)construction and its relation to social memory has been raised in The Bastard of Istanbul , written by one of the most prolific novelists Elif Shafak. The novel narrates how Turkey attempts to blot out people’s collective remembrance upon the violent history of the Armenian Genocide. The story depicts the issue by showing individuals with contradictory identities of Turks and Armenian Americans who live in a dilemmatic intersection of ignoring and keeping such a memory. This article describes the identity (re)construction among Istanbulites, including Turks and Armenians, as two competing (id)entities, as depicted in The Bastard of Istanbul . The study is a literary criticism that focuses on the social issue of identity (re)construction. It applies Castells' (2010) theory of identity construction and Misztal's idea of social memory (2003). This study reveals that Turkish-ness identity (re)construction of the Istanbulites characters comprises three significant components of legitimation, resistance, and projection that interfere with the competing identities of Turks and Armenians.